In vitro medium-term conservation of Bacopa monnieri (L.) Pennell-The Memory Plus plant-under slow-growth conditions - George, S.=700 1 Geetha S.P.; Sudhakar Raja, S.
(En, Fr, Es)
Ilus., 26 ref.
Keywords: CULTIVO IN VITRO; RECURSOS GENETICOS; PLANTAS MEDICINALES; ITALIA; BACOPA MONNIERI